PERAN HIPOKSIA PADA PATOGENESIS PENYAKIT GINJAL - Sastrawan, I Gede Pande; Suwitra, Ketut (journal of internal medicine, 2008)
Chronic kidney disease is a current major worldwide health problem with an increasing prevalency.Kidney is a sensitive organ with hypoxic condition relate to its high tubular epithelial cells and vascular oxygenconsumption. Chronic peritubular ischemia may occur through several interrelating mechanisms. The activationof local renin-angiotensin system, angiotensin II, could induce hypoxia by means of hemodinamic and nonhemodinamicmechanisms.Anemia in renal disease could accelerate the decline of renal function through the induction oftubulointerstitial hypoxia. Non Steroidal Anti Inflamatory Drugs (NSAID) could evoke renal medullar hypoxiaby its regional hypoperfusion mechanism and the escalation of tubular transport. The Outer region of renalmedulla and tubulus are main target of hypoxic renal damage. The mechanism of hypoxia induced AcuteKidney Disease involves renal vascular and tubulus through the reduction of blood flow and the increasing oftubular oxygen demands. The Patofisiology of hypoxia induced chronic kidney disease occurs bytubulointerstitial damage which induce fibrogenesis, causing interference of peritubular blood flow and oxygenconsumption.